Fostering Pathways and Creativity Responsible for Advancing Health Research Skills and Knowledge for Healthcare Professionals to Heighten Evidence-Based Healthcare Practices in Resource-Constrained Healthcare Settings - Nzayikorera, Janvier (Journal of Community Medicine and Health Solutions, 2025)
Globally, evidence-based healthcare practices are the most dependable framework for effective healthcare decisions and practices. In all nations, financial resources, people, and time are always insufficient. Healthcare professionals should recommend healthcare interventions that have been proven to be safe, effective, and affordable. All healthcare professionals must be creative to be involved in the creation and compilation of trustworthy evidence to support the decrease in morbidity and mortality of communicable and non-communicable diseases, particularly in developing nations. Regretfully, most developing nations still exhibit weaknesses and barriers to promoting health research and evidence-based healthcare. Evidence indicates that developing countries contribute 1% - 2% of health research activities to address global health problems and challenges. As a result, many individuals in these nations continue to have below-average health conditions. The lack of creativity, innovation, and motivation to gain health research competencies for healthcare professionals causes all these issues. Creativity and innovation are the foundations for the effective implementation of evidence-based healthcare. Surprisingly, no researchers have explored how creativity and innovation heighten evidence-based healthcare practices. The primary objective of this project will be to foster pathways and explore the creativity that advances health research abilities among healthcare professionals to improve evidence-based healthcare practices in resource-limited healthcare settings.